TEMPOROMANDIBULAR JOINT DISORDERS IN THE ELDERLY: A LITERATURE REVIEW - Susanna Halim; Sharon Altin Taqwani (HEALTHY : Jurnal Inovasi Riset Ilmu Kesehatan, 2026)
ABSTRACT Temporomandibular joint (TMJ) disorder is one of the orofacial problems often found in the elderly due to degenerative changes, decreased musculoskeletal function, and systemic conditions that accompany the aging process. Elderly people tend to experience decreased tissue elasticity, bone resorption, tooth loss, and the use of dentures that can affect the stability and function of the temporomandibular joint. The aim is to examine the characteristics, risk factors, clinical manifestations, and management of TMJ disorders in the elderly. Literature search methods from various national and international scientific databases with keywords related to TMJ disorders and the elderly. Selected articles include observational studies, case reports, and relevant review studies. Results and Discussion show that TMJ disorders in the elderly are generally characterized by joint pain, limited mouth opening, joint sounds, and impaired masticatory function that can impact quality of life. Frequently reported predisposing factors include posterior tooth loss, occlusal imbalance, degenerative changes in the joints, and systemic diseases such as osteoarthritis. Management of TMJ disorders in the elderly needs to consider the general condition of the patient and be conservative, including education, pharmacological therapy, physiotherapy, and the use of occlusal appliances if necessary. Conclusion: TMJ disorders in the elderly are multifactorial conditions that require a holistic and individual approach to improve the function and quality of life of patients. ABSTRAK Gangguan sendi temporomandibular (TMJ) adalah salah satu masalah orofasial yang sering ditemukan pada lansia karena perubahan degeneratif, penurunan fungsi muskuloskeletal, dan kondisi sistemik yang menyertai proses penuaan. Lansia cenderung mengalami penurunan elastisitas jaringan, resorpsi tulang, kehilangan gigi, dan penggunaan gigi palsu yang dapat memengaruhi stabilitas dan fungsi sendi temporomandibular. Tujuannya adalah untuk meneliti karakteristik, faktor risiko, manifestasi klinis, dan penanganan gangguan TMJ pada lansia. Metode penelusuran literatur dari berbagai basis data ilmiah nasional dan internasional dengan kata kunci yang berkaitan dengan gangguan TMJ dan lansia. Artikel yang dipilih meliputi studi observasional, laporan kasus, dan studi tinjauan yang relevan. Hasil dan Diskusi menunjukkan bahwa gangguan TMJ pada lansia umumnya ditandai dengan nyeri sendi, keterbatasan pembukaan mulut, bunyi sendi, dan gangguan fungsi pengunyah yang dapat memengaruhi kualitas hidup. Faktor predisposisi yang sering dilaporkan meliputi kehilangan gigi posterior, ketidakseimbangan oklusi, perubahan degeneratif pada sendi, dan penyakit sistemik seperti osteoartritis. Penanganan gangguan TMJ pada lansia perlu mempertimbangkan kondisi umum pasien dan bersifat konservatif, termasuk edukasi, terapi farmakologis, fisioterapi, dan penggunaan alat oklusal jika diperlukan. Gangguan TMJ pada lansia merupakan kondisi multifaktorial yang membutuhkan pendekatan holistik dan individual untuk meningkatkan fungsi dan kualitas hidup pasien.